2010
DOI: 10.1111/j.1523-5378.2010.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mucin Lewis Status in Resistance to Helicobacter pylori Infection in Pediatric Patients

Abstract: Background Helicobacter pylori causes gastritis, peptic ulcer and is a risk factor for adenocarcinoma and lymphoma of the stomach. Gastric mucins, carrying highly diverse carbohydrate structures, present functional binding sites for H. pylori and may play a role in pathogenesis. However, little information is available regarding gastric mucin in children with and without stomach diseases. Material & Methods Expression of mucins and glycosylation was studied by immunohistochemistry on gastric biopsies from 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 50 publications
5
45
1
Order By: Relevance
“…The presence of GlcNAc may signal to the pathogen that it is in the mucus niche, and downregulating such factors may in turn free up more resources for growth. Indeed, in the human stomach, evidence suggests that downregulating pathogen binding to the gastric mucins is beneficial for the pathogen, as its removal from the gastric niche is decreased (43), and the pathogen decreases the level of adhesins after culture with mucins carrying the ligand to which it adheres (44).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of GlcNAc may signal to the pathogen that it is in the mucus niche, and downregulating such factors may in turn free up more resources for growth. Indeed, in the human stomach, evidence suggests that downregulating pathogen binding to the gastric mucins is beneficial for the pathogen, as its removal from the gastric niche is decreased (43), and the pathogen decreases the level of adhesins after culture with mucins carrying the ligand to which it adheres (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that H. pylori-infected children presented a normal pattern of expression and glycosylation of mucin 5AC (MUC5AC) in the surface mucous cells, and MUC6 in the gland mucous cells, contrasting with the aberrant expression of MUC6 and MUC2 found in infected adults. Additionally, it was shown that the pattern of Lewis blood group antigens in the surface epithelium of children was significantly correlated with H. pylori load, however no correlation with gastritis, nodularity, and gastric or duodenal ulcer was found [17].…”
Section: Host Susceptibilitymentioning
confidence: 99%
“…Nevertheless, H. pylori-associated peptic ulcer disease may also occur shortly after infection in childhood [4][5][6][7][8]. This rare event may be due to more virulent strains [9][10][11][12][13][14][15][16], and/or more predisposed subjects [17][18][19]. The two forms of H. pylori-associated peptic ulcers, i.e., gastric ulcer and duodenal ulcers, are divergent in prevalence and physiopathology, but both cause considerable patients' morbidity entailing high annual costs of treatment [93].…”
Section: Peptic Ulcer -Related Organic Dyspepsia In Paediatrics a Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Normal gastric mucosa shows cell type specific expression of secreted mucin MUC5AC in the surface epithelium (Wang et al, 2006;Lindén et al, 2010). Several studies have strongly suggested that MUC5AC forms the major receptor for H. pylori in the human stomach (Van de Bovenkamp et al, 2003;Lindén et al, 2008), and the infection of H. pylori can alter the expression of MUC5AC (Kocer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%